2014
DOI: 10.1007/s13524-014-0323-8
|View full text |Cite
|
Sign up to set email alerts
|

Rural-to-Urban Migration and Sexual Debut in Thailand

Abstract: Migration from one’s parents’ home and sexual debut are common features of the transition to adulthood. Although many studies have described both of these features independently, few have examined the relationship between migration and sexual debut in a systematic manner. In this study, we explore this link for young adults in Thailand. With relatively high rates of internal migration, rapid modernization, a moderate HIV epidemic, and a declining average age of sexual debut, Thailand presents an instructive en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“… 3 Anglewicz et al (2014) found a relationship between rural-to-urban migration and timing of sexual debut, using the same data from Thailand. …”
mentioning
confidence: 89%
“… 3 Anglewicz et al (2014) found a relationship between rural-to-urban migration and timing of sexual debut, using the same data from Thailand. …”
mentioning
confidence: 89%
“…Findings may have resulted due to defined social expectations based on specific gender and racial groups as defined in different cultures and communities (Cavazos-Rehg et al, 2009; Kinsman, Romer, Furstenberg, & Schwarz, 1998). Age (Jordahl & Lohman, 2009), income (Dinkelman, Lam, & Leibbrandt, 2007; Valle, Roysamb, Sundby, & Klepp, 2009), education (De Graaf, Vanwesenbeeck, & Meijer, 2014; Dinkelman et al, 2007), and marital status (Anglewicz, VanLandingham, & Phuengsamran, 2014) have also been shown to be associated with sexual debut.…”
Section: Introductionmentioning
confidence: 99%
“…. In the city, these young people are exposed to different social norms to those in rural areas, with these new norms shaping their experience of the city as they become more independent in an urban environment (Anglewicz, VanLandingham, and Phuengsamran 2014;Ma and Cheng 2005).…”
mentioning
confidence: 99%
“…At the same time, migration, economic participation, increased independence and exposure to new ideas can help young women challenge entrenched oppressive gender norms (Yeoh 2016). Challenging gender relations may extend to exploring different ways of creating intimate relationships and sexual encounters, potentially developing more control over their bodies, but also potentially exposing them to new sexual vulnerabilities, the risk of sexually transmitted infections (STIs) and unplanned pregnancy (Swasti Centre 2018; Anglewicz, VanLandingham, and Phuengsamran 2014;Ma and Cheng 2005;Lyttleton 2014; Sychareun et al 2016;Sychareun et al 2018). Studies have found, for example, an association between rural-to-urban migration and early sexual debut (Mberu and White 2011;Luke et al 2012), increased sexual activity, increased numbers of sexual partners and unprotected sex (Anglewicz, VanLandingham, and Phuengsamran 2014;Gaetano and Jacka 2004;Welz et al 2007) and increased gender-based violence (Gaetano and Jacka 2004;Anglewicz 2012;Philip, Mark and Dusita 2014;Yeoh 2016).…”
mentioning
confidence: 99%